An ultraviolet photoelectron spectroscopy study on bandgap broadening of epitaxial graphene on SiC with surface doping. (February 2020) - Hu, Yanfei; Liu, Jialin; Dou, Wentao; Mao, Kaili; Guo, Lixin; Chong, Laiyuan; Hu, Jichao; Yuan, Hao; He, Yanjing; Guo, Hui; Zhang, Yuming
Abstract: The bandgap of epitaxial graphene thermally grown on 4H–SiC(0001) can be widened via a novel charge transfer mechanism by modifying the buffer layer and surface of SiC with substrate doping before epitaxial graphene growth. High-resolution photoemission spectroscopy base on synchrotron radiation reveal that the bandgap broadening of epitaxial graphene is attributed to modification of buffer layer between epitaxial graphene and the substrates, and both donor-acceptor and bulk atoms injected in the SiC make the bandgap of EG on those substrates broaden. This novel bandgap broadening mechanism via substrates doping will provide a simple and effective approach to nondestructively broad the bandgap of epitaxial graphene for future electronics application. Graphical abstract: Image 1